2021
DOI: 10.3390/ijms22137060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 13 Guanidinobenzoyl- or Aminidinobenzoyl-Containing Drugs to Potentially Inhibit TMPRSS2 for COVID-19 Treatment

Abstract: Positively charged groups that mimic arginine or lysine in a natural substrate of trypsin are necessary for drugs to inhibit the trypsin-like serine protease TMPRSS2 that is involved in the viral entry and spread of coronaviruses, including SARS-CoV-2. Based on this assumption, we identified a set of 13 approved or clinically investigational drugs with positively charged guanidinobenzoyl and/or aminidinobenzoyl groups, including the experimentally verified TMPRSS2 inhibitors Camostat and Nafamostat. Molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…To further explore the specific binding sites where RES plays the above roles, we performed molecular docking validation. Generally, results of molecular docking are mainly evaluated by minimum binding free energy (Delta G) [ 39 ]. The lower the binding energy is, the less energy is required for the drug molecule to bind with the target, and it indicates a greater binding possibility and stability [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the specific binding sites where RES plays the above roles, we performed molecular docking validation. Generally, results of molecular docking are mainly evaluated by minimum binding free energy (Delta G) [ 39 ]. The lower the binding energy is, the less energy is required for the drug molecule to bind with the target, and it indicates a greater binding possibility and stability [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The superimposition of previously published SARS-CoV-2 3CL-pro structures with bound GC376 is shown in Figure 3 d. N3, formerly known as the Michael acceptor inhibitor, was created with a computer-aided method. N3 has shown significant antiviral efficacy against infectious bronchitis viruses in an animal model and can selectively inhibit the Mopar of numerous coronaviruses, including SARS-CoV and MERS-CoV [ 56 , 57 , 58 ]. SARS-CoV-2 3CLpro was demonstrated to establish a covalent link with N3, acting as an irreversible inhibitor of SARS-CoV and MERS-CoV 3CLpro.…”
Section: Inhibitorsmentioning
confidence: 99%
“…In a clinical trial, Foipan™ [( N , N -dimethylcarbamoylmethyl (4-(4-guanidinobenzoyloxy)-phenylacetate)) methanesulfate] [ 51 ], also known as camostat mesylate (NI-03; CAS number: 59721-28-7), was administered at a dose of 200 mg three times a day for 2 weeks to 95 patients to investigate its effect against dyspepsia associated with non-alcoholic mild pancreatic disease; the drug showed mild, but no serious, adverse effects, which indicated that camostat mesylate was a well-tolerated medicine [ 51 , 52 ].…”
Section: Therapeutic Approaches To Sar-cov-2 Infectionmentioning
confidence: 99%
“…N3, formerly known as Michael acceptor inhibitor, was developed using a computer-aided method. N3 can specifically inhibit the Mpro of multiple coronaviruses, including SARS-CoV and MERS-CoV, and has shown potent antiviral activity against infectious bronchitis virus in an animal model [ 51 , 52 , 61 ]. N3 was shown to form a covalent bond with SARS-CoV-2 3CLpro, thereby acting as an irreversible inhibitor of SARS-CoV and MERS-CoV 3CLpro [ 51 , 52 ].…”
Section: Therapeutic Approaches To Sar-cov-2 Infectionmentioning
confidence: 99%